Hygromechanical strains during the drying of Eucalyptus nitens boards - Pérez-Peña, N.; Cloutier, A.; Segovia, F.; Salinas-Lira, C.; Sepúlveda-Villarroel, V.; Salvo-Sepúlveda, L.; Elustondo, D.M.; Ananías, R. A. (Maderas. Ciencia y Tecnología, 2016)
Collapse and drying stresses are currently induced during the drying of Eucalyptus nitens in solid wood products. The purpose of this study was to investigate these drying stresses by measuring hygromechanical strains during the drying of Eucalyptus nitens boards. Small samples of Eucalyptus nitens wood were oriented in the radial and tangential directions and tested to determine the hygromechanical strains during the drying process. This experimental work consisted of cantilevered bending tests conducted under variable relative humidity conditions. Tests were performed in a conditioning chamber at 30 °C with an equilibrium moisture content ranging from 22 to 12% under four levels of stress: 0, 10, 20 and 30% of the rupture load. The strains were determined using strain gauges, and the total deflection was measured with a linear variable differential transformer. The results show that in hygromechanical strains during the drying of Eucalyptus nitens, both the surface deformation and mechano-sorption strain were found to be proportional to the applied stress and reached their maximum values in the tangential direction. The total deflection increased 0,18 mm/mm with a surface deformation of 0,20 mm/mm, and the mechano-sorptive strain provides a greater contribution with a value of 0,11 mm/mm, thus corresponding to 59% of the total deformation. In attempts to improve the drying schedules of Eucalyptus nitens to develop solid wood products, mechano-sorptive behavior may be applied to relieve collapse and drying stress.